PENGARUH KOMPENSASI KEUANGAN DAN NON KEUANGAN TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA KARYAWAN KOPERASI PEGAWAI PT“X” MADIUN - Liliek Nur Sulistyowati (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2014)
In global competition, the presence of qualified human resources has a role that is more than other resources. Today many organizations or companies that have a setting for human resources, known as Human Resource Management (HRM). Management is very important to the organization or company to manage and organize their employees to be able to work productively to achieve the goals of the organization or company, as an organization in general, then in Employees Cooperative PT “X” Madiun also required an increase to employee performance. An employee or the employee will feel pride and satisfaction with the performance achieved. The variables used in this research is financial compensation (X1), non-financial compensation (X2), employee performance (Z) and job satisfaction (Y). Measurement of variables using Likert scale, with a total sample of 108 people. The model used to analyze the data in this study is path analysis. Based on the results of research found that financial and non financial compensation has a positive and significant impact on job satisfaction, as well as financial and non financial compensation have positive and significant impact on employee performance and job satisfaction have a positive and significant impact on employee performance.